Integrating theoretical-practical knowledge: challenges and prospects at interdisciplinary work in the Languages Course - Santos, Leandra Ines Seganfredo; Precioso, Adriana Lins; Melo, Ariane Macedo (The ESPecialist, 2015)
The article describes and discusses pre-service teacher education to language teaching from the experience of an interdisciplinary project. The data comes from a group of students enrolled in the sixth semester of Letters at the University of the State of Mato Grosso, Campus of Sinop, and were collected from the proposed activities and teachers’ own pedagogical practice. The results show that initial education, through a reflexive proposal that enables the relationship between theory and practice, is desired by future professionals and reflects a more significant experience because they feel better prepared for the pedagogical work in the classroom.